EMOTIONALLY-EFFECTIVE DISORDERS IN PATIENTS WITH ARTERIAL HYPERTENSION - Nikolaychik, A.M.; Kozlova, Yu.V.; Kolesnik, T.V. (The Ukrainian Scientific Medical Youth Journal, 2018)
The aim of the work was to study the effect of high blood pressure and stress factors in the psycho-emotional state of elderly patients. Ground the pathogenic mechanism of affective disorders in patients with arterial hypertension. The materials and methods. 45 patients were examined. They were divided into two groups – primary and control. The main group includes 28 patients diagnosed with GD of stage III, aged 60 to 95 years (83 ± 1.09 years). In the main group of 20 patients (72%) had a combination of GD with ischemic heart disease and angina pectoris (the III functional class), in 4 (14%) patients with GD was complicated by postinfarction cardiosclerosis, in 4 (14%) – cerebral circulation disorder. The control group consisted of 17 normotensive patients without cardiovascular diseases, in age from 61 to 77 years (67.8 ± 0.93 years). Groups were matched according to the age and gender of the patients. The results. This research showed the significant differences between two control groups of patients. In patients with arterial hypertension, the level of anxiety is increased on 20%, depression on 27% and stress on 27%. Stress in this work can be considered as a risk factor for the development of permanent increase of blood pressure due to the activation of the sympathoadrenal system. That is lead to a negative effect of arterial hypertension on the dorsolateral frontal cortex due to pathological changes in the structure of the vascular wall. Was detected an increase in anxiety level on 20%, depression and stress on 27%, respectively, in the main observation group. Conclusion. The information received during the course of this work, definitely, requires more extensive clinical studies, but indicate some dependence of the influence of arterial hypertension on the structure of the brain. Primarily it is affecting on the striatal complex and dorsolateral frontal cortex, which lose certain connections during the disorders. Moreover, in the elderly patients of the main group, there is a cerebral blood supply disorder, which leads to cognitive dysfunctions and in the future may cause geriatric dementia.